Lenalidomide as second‐line therapy for advanced hepatocellular carcinoma: exploration of biomarkers for treatment efficacy - Shao, Y.‐Y.; Chen, B.‐B.; Ou, D.‐L.; Lin, Z.‐Z.; Hsu, C.‐H.; Wang, M.‐J.; Cheng, A.‐L.; Hsu, C. (Alimentary pharmacology & therapeutics, 2017)
Background Lenalidomide has immunomodulatory and anti‐angiogenic effects and showed moderate anti‐tumour efficacy in patients with. advanced hepatocellular carcinoma (HCC) Aim To explore potential biomarkers of lenalidomide efficacy as second‐line therapy for HCC. Methods Eligible patients were diagnosed with advanced HCC, documented progression on sorafenib, and Child‐Pugh class A liver function. Patients received 25 mg/day lenalidomide orally on days 1‐21 every 4 weeks. The primary endpoint was 6 month progression‐free survival rate. Early α‐fetoprotein response was defined as a > 20% decline of α‐fetoprotein levels from baseline within the first 4 weeks of treatment. Vascular response, evaluated using dynamic contrast‐enhanced magnetic resonance imaging, was defined as a > 40% decline in Ktrans after 2 weeks of treatment. The percentage of peripheral blood lymphocyte subsets were also analysed. Results Fifty‐five patients were enrolled. The response rate was 13%, and the disease‐control rate was 53%. The 6 month progression‐free survival rate was 9.1%. The median progression‐free and overall survival was 1.8 months and 8.9 months respectively. Early α‐fetoprotein response was significantly associated with higher disease‐control rate (76% vs 22%, P = .001) and longer progression‐free survival (P = .020). Vascular response was not associated with any treatment outcomes. Patients with a high pre‐treatment B cell percentage were more likely to have disease control (70% vs 36%, P = .010) and exhibited longer progression‐free survival (P < .001) and overall survival (P = .042). Conclusions Lenalidomide exhibited moderate activity as second‐line therapy for advanced HCC. Its immunomodulatory effects should be further explored (www.clinicaltrials.gov NCT01545804).